Inside Back Cover: Motion‐Based, High‐Yielding, and Fast Separation of Different Charged Organics in Water (ChemPhysChem 1/2015). Issue 1 (12th January 2015) - Xuan, Mingjun; Lin, Xiankun; Shao, Jingxin; Dai, Luru; He, Qiang
<x xml:space="preserve">Abstract</x> The cover picture shows a self‐propelled Janus silica micromotor as a motion‐based analytical method for achieving fast target separation of polyelectrolyte microcapsules, enriching differently charged organics with low molecular weights in water. As described on p. 147 by L. Dai, Q. He, et al., this method could potentially be used for water‐quality monitoring and analysis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>